Formulation of Micro Product Positioning Strategy - Sewaka, Iman; Marsono, Acong Dewantoro (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the strategic alignment of microfinance products following the integration of PNM, Pegadaian, and BRI into the Ultra Micro Holding (UMi). A primary focus is the standardization of micro-segment products to avoid overlap and strengthen the ecosystem. The analysis highlights similarities among BRI’s KUPEDES, Micro Pegadaian, and PNM’s ULaMM products, emphasizing the impact on ULaMM’s conventional individual lending. Identifying product overlaps and conducting comparative feature analysis is essential for continuous product improvement. The study employs a qualitative approach to: (1) analyze product feature comparisons, (2) assess customer satisfaction performance, (3) investigate the background of product feature overlaps, and (4) formulate a customer-driven development and positioning strategy. Findings aim to present a Sustainable Competitive Advantage using strategic management tools. Key informants and structured timelines are designed to minimize respondent disruption while collecting insights for product differentiation. A SWOT analysis of PNM’s Business Model Canvas post-integration will inform strategic initiatives for growth over the next five years. Effective marketing programs must communicate the desired product perception, while the company prepares for potential digital transitions to enhance technology readiness and customer experience management. Addressing operational gaps and aligning human capital within the holding is crucial for fostering stakeholder engagement and sustainable growth.